Binocular function during unequal monocular input. (25th January 2017) - Kim, Taekjun; Freeman, Ralph D.
Abstract: The fine task of stereoscopic depth discrimination in human subjects requires a functional binocular system. Behavioral investigations show that relatively small binocular abnormalities can diminish stereoscopic acuity. Clinical evaluations are consistent with this observation. Neurons in visual cortex represent the first stage of processing of the binocular system. Cells at this level are generally acutely sensitive to differences in relative depth. However, an apparent paradox in previous work demonstrates that tuning for binocular disparities remains relatively constant even when large contrast differences are imposed between left and right eye stimuli. This implies a range of neural binocular function that is at odds with behavioral findings. To explore this inconsistency, we have conducted psychophysical tests by which human subjects view vertical sinusoidal gratings drifting in opposite directions to left and right eyes. If the opposite drifting gratings are integrated in visual cortex, as wave theory and neurophysiological data predict, the subjects should perceive a fused stationary grating that is counter‐phasing in place. However, this behavioral combination may not occur if there are differences in contrast and therefore signal strength between left and right eye stimuli. As expected for the control condition, our results show fused counter‐phase perception for equal inter‐ocular grating contrasts. Our experimental tests show a striking retention of counter‐phase perception even for relatively large differences in inter‐ocular contrast. This finding demonstrates that binocular integration, although relatively coarse, can occur during substantial differences in left and right eye signal strength. Abstract : This paper resolves a conflict between previous psychophysical and neurophysiological data concerning binocular function when image quality between left and right eyes is unequal. We demonstrate via psychophysical tests that there is a basic form of binocular function even when image quality is substantially different for left and right eyes. Panel A of the figure shows a mirror haploscope which is used to present two separate views to each eye. Binocular fusion of two opposite drifting gratings induces a perception of a counter‐phase flickering grating.